Analysis of the slope of isentropic surfaces and its tendencies over the North Atlantic. (8th September 2015) - Papritz, Lukas; Spengler, Thomas
Abstract : The maintenance of baroclinicity along mid‐ and high‐latitude storm tracks is a matter of ongoing debate. Using an isentropic framework, a novel diagnostic based on the tendency equation for the slope of isentropic surfaces – a measure of the potential for baroclinic development – is presented. The tendency comprises contributions from dynamic processes, latent heat release, radiation and subgrid‐scale turbulence, which incorporates the effect of sensible heat fluxes. A climatology of these tendencies over the North Atlantic is compiled for the winters of 2009 and 2010. It is found that adiabatic tilting flattens the isentropic surfaces, reflecting the action of growing baroclinic cyclones. This tendency is balanced climatologically by the generation of slope by diabatic processes. In the lower troposphere, the most intense diabatic increase of slope is found along the oceanic frontal zone associated with the Gulf Stream and at higher latitudes in the Labrador Sea, the Nordic Seas and the Barents Sea. Latent heat release and sensible heat fluxes both contribute substantially in these regions. A quantitative analysis of cold‐air outbreaks emphasizes their important role in restoring the slope in the lower troposphere over the Gulf Stream region and off the sea‐ice edge at high latitudes. In the upper troposphere, latent heat release due to cloud microphysical processes is the dominant mechanism maintaining the slope. Abstract : Sloping isentropic surfaces are a prerequisite for baroclinic instability. In general, baroclinic instability tends to flatten isentropic surfaces (blue and black arrows), but isentropic upglide (gray arrow) can lead to cloud formation and associated latent heat release, which also acts to deform isentropic surfaces. In addition, warming by upward sensible heat fluxes (red arrow) over warmer waters causes a steepening. In this study, we introduce a diagnostic framework that allows us to quantify the contributions of diabatic and adiabatic processes that change the slope of isentropic surfaces. This framework is applied to North Atlantic winter conditions.